Effect of watercress extract supplementation on lipid profile and oxidative stress markers in overweight people with physical disability: A randomized, double‐blind, and placebo‐controlled trial. (28th January 2021) - Clemente, Mirna; Miguel, Marilis D.; Felipe, Karina B.; Gribner, Caroline; Moura, Paula F.; Rigoni, Ana A. R.; Parisotto, Eduardo B.; Henneberg, Railson; Dias, Josiane de Fatima Gaspari; Piltz, Marina T.; Clemente, Erick F.; Schonhofen, Christian B.; et al.
Abstract : Studies have demonstrated that diet rich in cruciferous vegetables of the Brassicaceae family can reduce the risk of cardiovascular diseases and oxidative stress levels. Nasturtium officinale (Brassicaceae ), commonly known as watercress is a perennial dicotyledonous plant usually found close to water. Although previous investigations have demonstrated the beneficial effects of watercress on hypercholesterolemia in animal studies, until now no such studies have been conducted with humans, up to this time. This study aimed to investigate whether overweight individuals were able to improve or maintain their serum lipid and oxidative stress markers when given standardized extract of Nasturtium officinale (SENO) as a supplement. This was a randomized, double‐blind, and placebo‐controlled trial conducted over 5 weeks. Thirty‐four overweight people with physical disabilities were selected randomly to participate in this study and then they were assigned randomly to two groups, one treated with 750 mg//kg/d of SENO and the other treated with 750 mg/kg/d of placebo. The results indicated that SENO caused a significant improvement in the levels of low‐density lipoprotein cholesterol, creatinine, and lipid peroxidation. However, SENO did not cause a significant statistical change in total serum cholesterol, triacylglycerol, and high‐density lipoprotein levels; catalase, superoxide dismutase, creatinine, alanine aminotransferase, aspartate aminotransferase, and urea parameters. The present data might provide supportive evidence that SENO did not cause any harm and positively affected low‐density lipoprotein cholesterol profile and creatinine as well as lipid peroxidation levels in the participants. Nevertheless, further studies are suggested to clarify the results presented in this clinical trial.